Asuhan Keperawatan Ansietas pada Remaja dengan Kekerasan Seksual - Pirez, Rosalina Gastao (Jurnal Pengabdian Kesehatan, 2024)
Adolescence is the most important period of human development, representing the human transition from childhood to adulthood. Adolescence experiences emotional changes that are proportional to the physical changes experienced. This triggers sexual attraction to the opposite sex. This event can lead to sexual violence in adolescents. Emotionally, victims of sexual violence experience stress, feelings of guilt, fear of connecting with others, and anxiety. The role of nurses is needed to help identify the anxiety experienced and the level of knowledge about sexual violence. This case study aims to describe changes in anxiety levels and levels of sexual knowledge before and after the intervention. Nurses provide nursing actions to 6 adolescent clients with anxiety. The results of the intervention proved a decrease in the level of anxiety in clients before and after being given nursing interventions.